2012
DOI: 10.1139/a11-021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on morphological, biochemical, and physiological aspects of plants and plant products

Abstract: Research on the basic interaction of radiation with biological systems has contributed to human society through various applications in medicine, agriculture, pharmaceuticals and in other technological developments. In the agricultural sciences and food technology sectors, recent research has elucidated the new potential application of radiation for microbial decontamination due to the inhibitory effect of radiation on microbial infestation. The last few decades have witnessed a large number of pertinent works… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
125
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(136 citation statements)
references
References 174 publications
2
125
0
9
Order By: Relevance
“…Gamma rays were employed to developed 64% of the radiation induced mutant varieties, followed by 22% by X-rays (IAEA, 2015) gamma rays is an energetic form of electromagnetic radiations are recognized as the widely used mutagen for their simple application, good penetration, reproducibility and high mutation frequency (Chahal and Gosal, 2002) gamma rays having short wavelength with high penetrable power, interact with atoms or molecules to produce free radicals in the cells. Among the physical mutagens, gamma ray stands first in its effectiveness in the induction of mutation in crop plants (Jan et al, 2011;Verma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma rays were employed to developed 64% of the radiation induced mutant varieties, followed by 22% by X-rays (IAEA, 2015) gamma rays is an energetic form of electromagnetic radiations are recognized as the widely used mutagen for their simple application, good penetration, reproducibility and high mutation frequency (Chahal and Gosal, 2002) gamma rays having short wavelength with high penetrable power, interact with atoms or molecules to produce free radicals in the cells. Among the physical mutagens, gamma ray stands first in its effectiveness in the induction of mutation in crop plants (Jan et al, 2011;Verma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of peanut seeds (Al-Bachir, 2015b). Extensive research has shown that protein did not exhibit signifi cant losses during irradiation even at doses of over 10 kGy (Jan et al, 2012). During storage (after 6 and 12 months), the moisture content increased signifi cantly (p < 0.01) in both control and irradiated peanut seeds and this increase was higher in the control samples compared to irradiated ones.…”
Section: Eff Ect Of Irradiation and Storage On Proximate Composition mentioning
confidence: 95%
“…The growth inhibition of embryo development can be evoked by the damage of the cells of embryo and the meristem tissues, also the damage of auxin activity that very sensitive to photo-oxidation or caused by disturbance of physiological activity. Inhibition of growth caused by genome damage and disruption of mitosis, mainly due to disruption of the cell cycle at the G2/ M phase (Jan et al 2012). Inhibition of growth rate can also be triggered due to the death of meristem cells, not only by the genetic damage.…”
Section: Effects Of X-ray Irradiation On the Growth Of Embryos And Sementioning
confidence: 99%
“…Inhibition of growth rate can also be triggered due to the death of meristem cells, not only by the genetic damage. The growth can also be suppressed by physiological disorders (De Micco and Arena 2011;Jan et al 2012). Gonzales et al (2008) was also found some inhibition of plantlets growth due to gamma-ray irradiation to the embryos of S. plicata.…”
Section: Effects Of X-ray Irradiation On the Growth Of Embryos And Sementioning
confidence: 99%
See 1 more Smart Citation